Ukraine’s investment climate analysis through the prism of projecting in the sphere of housing reconstruction: prospects in the conditions of economic revitalization - Fisunenko, Pavlo; Vakulich, Maria (Ways to Improve Construction Efficiency, 2024)
The application of the abstraction method allowed us to identify the characteristics of the conceptual principles of forming a favorable investment climate in the economic system of Ukraine, which made it possible to analyze the spectrum of investment design in the field of housing reconstruction in the context of economic revitalization. The article analyzes the volume of capital investments in the economy of Ukraine by financing sources, the volume of capital investments by types of economic activity by regions, and identifies the most priority investment projects in the construction sector by the volume of investment capital attracted. In the conditions of destabilization of the economic environment in Ukraine and the unpredictability of the development of its economic sphere, a comprehensive analysis of multidirectional phenomena and processes in the available options for their global manifestation is necessary. After all, the corresponding transformational transformations are gaining global significance and are a catalyst for structural and institutional shifts. In the conditions of active hostilities on the territory of Ukraine, the issue of reconstruction of the housing stock is one of the primary and strategically important for the functioning of the economic system of the state. Therefore, the issue of conducting a comprehensive analysis of the state of the investment climate of the Ukrainian economy through the prism of investment planning in the field of reconstruction of the housing stock is gaining priority. The following general scientific and applied research methods were used in the research process: analysis and synthesis, deduction and induction - in the process of selecting features that significantly complicate the process of effectively forming the features of investment planning in Ukraine; systematization and generalization - in the process of analyzing the research question among groups of scientists both in Ukraine and abroad; monographic methods - for in-depth study of the tasks set; abstract-logical methods - for theoretical generalization of research results and formulation of conclusions and proposals. The originality lies in substantiating the list of main obstacles and risks of low investment activity in the field of housing reconstruction in Ukraine, which consist in the imperfection of the institutional environment. The corresponding situation causes a violation of the conditions of competitiveness of the domestic economy in the field of housing; insufficient development of the domestic real estate market in Ukraine; growth of inflation, which leads to the depreciation of savings of the population; formation of a low level of protection of additional capital of a potential investor and other key problematic aspects that form a general negative synergistic effect when analyzing the state of the investment climate of the economic system of the state.